Penyebab Kenakalan Remaja di Cipongkor - Wianda Aulia; Ageng Saepudin Kanda S (Universitas 45 Surabaya, 2024)
Juvenile delinquency is a deviant behavior carried out by young people, this behavior is often found, namely smoking, drinking alcohol, stealing, free sex and gathering until late at night, this is contrary to the law, religious teachings and social norms so that it can disturb the surrounding environment, So this is important to research. Interpersonal communication is considered the most effective for guiding and changing someone's behavior. Children are the responsibility of parents, parents need to prevent juvenile delinquency from occurring. Based on these conditions, research was conducted regarding interpersonal communication between parents and children in preventing juvenile delinquency and to determine parental barriers in preventing juvenile delinquency.